Late Holocene droughts in the Fertile Crescent recorded in a speleothem from northern Iraq. Issue 3 (15th February 2017) - Flohr, Pascal; Fleitmann, Dominik; Zorita, Eduardo; Sadekov, Aleksey; Cheng, Hai; Bosomworth, Matt; Edwards, Lawrence; Matthews, Wendy; Matthews, Roger
Abstract: Droughts have had large impacts on past and present societies. High‐resolution paleoclimate data are essential to place recent droughts in a meaningful historical context and to predict regional future changes with greater accuracy. Such records, however, are very scarce in the Middle East in general, and the Fertile Crescent in particular. Here we present a 2400 year long speleothem‐based multiproxy record from Gejkar Cave in northern Iraq. Oxygen and carbon isotopes and magnesium are faithful recorders of effective moisture. The new Gejkar record not only shows that droughts in 1998–2000 and 2007–2010, which have been argued to be a contributing factor to Syrian civil war, were extreme compared to the current mean climate, but they were also superimposed on a long‐term aridification trend that already started around or before 950 C.E. (Common Era). This long‐term trend is not captured by tree ring records and climate models, emphasizing the importance of using various paleoclimate proxy data to evaluate and improve climate models and to correctly inform policy makers about future hydroclimatic changes in this drought‐prone region. Key Points: A long‐term drying trend was present in the Fertile Crescent from at least 950 C.E. The recent droughts were extreme compared to the mean climate and superimposed on the long‐term aridification The long‐term trend is not captured by tree ring records or climate models